PENGARUH KARAKTERISTIK PEKERJAAN DAN KOMPENSASI TERHADAP KOMITMEN ORGANISASI PADA PT â€œXâ€ JAKARTA - Handaru, Agung Wahyu; Abdillah, Shalahudin; Waspodo, Agung AWS (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2013)
The purposes of this research are: 1) to describe the job characteristics, the compensation, and the organizational commitment, 2) to analyze the influence of job characteristics towards organizational commitment, 3) to analyze the influence of compensation towards organizational commitment, 4) to analyze the influence of job characteristics and compensation simultaneously toward organizational commitment. Population of the research is the employees of PT â€œXâ€, Jakarta. Samples of the research are 74 permanent employees. Type of the research is descriptive research and the method is explanatory survey. Descriptive analysis results showed: a) 49% total of permanent staff of PT "X" was not the realization the suitable of the job characteristics, b) 51% total of permanent staff of PT "X" was obtained compensation given by the organization was not good enough, c) 61% permanent employees of PT "X" has a relatively poor organizational commitment. The results of hypothesis testing: 1) there is a significant influence of job characteristics towards organizational commitment, 2) there is a significant influence of compensation towards organizational commitment, 3) job characteristics and compensation simultaneously having an influence on the organizational commitment. Determination coefficient score (R2) for X1 and X2 is 0.127, it means organizational commitment can be influenced by job characteristics and compensation around 12,7%, then other factors around 87,3%. Keywords: job characteristics, compensation, organizational commitment